Emergent Surgical Intervention for Embolization of Atrial Septal Defect Closure Device - Kim, Young Hak (Korean Society for Thoracic and Cardiovascular Surgery, 2012)
The percutaneous transcatheter closure of secundum atrial septal defect has recently become an increasingly widespread alternative to surgical closure in many centers. Although immediate, short, and intermediate term results of percutaneous transcatheter septal closure are promising, the procedure is not free from inherent complications that could be lethal. We report a case of device embolization necessitating emergent surgical retrieval.